Dano ao DNA no diabetes tipo 2 e sua associação com inflamação, estresse oxidativo, disfunção endotelial, resistência à insulina e à ocorrência de complicações crônicas microvasculares - Tatsch, Etiane (2016)
Several pathophysiological mechanisms are associated with type 2 diabetes mellitus (type 2 DM), such as glucotoxicity, insulin resistance, inflammation, oxidative stress and endothelial dysfunction, which can result in DNA strand breakage and changes in the nitrogenous bases. In this manner, DNA damage biomarkers may be useful in elucidating the pathophysiology of diabetes, as well as serving as an alternative to better evaluate its chronic complications. However, a great number of pathophysiological mechanisms related to increased DNA damage in diabetes need to be clarified. Thus, the objective of this study was to evaluate DNA damage in type 2 diabetes and its association with inflammation, oxidative stress, endothelial dysfunction, resistance towards insulin and the occurrence of chronic microvascular complications. The DNA damage was evaluated through the comet assay and the levels of 8-hydroxy-2'-deoxyguanosine (8-OHdG) urinary, the inflammatory process through the serum levels of interleukin (IL) 1, 6 and 10 and the alpha tumor necrosis factor (TNF-α), protein oxidation through plasma levels of advanced oxidation protein products (AOPPs), endothelial dysfunction by serum levels of NOx (nitrite/nitrate) and urinary albumin and insulin resistance through the index HOMA-IR. The present study was carried out in two phases. In the first phase, 32 patients with type 2 DM and 30 healthy individuals (control) were investigated. In the second phase, 54 patients with type 2 DM and 22 healthy individuals (control) were recruited from the University Hospital of Santa Maria (HUSM). This study found that patients with type 2 diabetes showed increased DNA fragmentation, assessed by comet assay, and increased oxidative DNA damage, assessed by 8-hydroxy-2'-deoxyguanosine (8-OhdG) urinary levels, compared to healthy control subjects. Additionally, increased DNA damage was observed in the type 2 DM group with inadequate glycemic control. When the areas obtained under the ROC curve were analyzed, 8-OHdG urinary presented higher diagnostic ability in identifying microvascular chronic complications compared with urinary albumin in the type 2 DM group. Furthermore, it was demonstrated that type 2 diabetic patients with microvascular complications had higher levels of oxidative DNA damage compared to patients without such complications. Interestingly enough, it was observed that type 2 diabetic patients with increased DNA damage had higher levels of proinflammatory cytokines such as IL-1, IL-6 and TNF-α, and a decrease in IL-10 levels, which is considered an anti-inflammatory cytokine. An association between increased DNA damage in type 2 diabetes and the index HOMA-IR, AOPPs levels and NOx levels and urinary albumin was also verified. Patients with type 2 diabetes exhibited factors that can directly contribute to the increase of DNA damage, such as insulin resistance, inflammation, endothelial dysfunction and increased generation of reactive species.